2022
DOI: 10.1038/s41380-022-01736-y
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone as a potential new pharmacotherapy for alcohol use disorder: convergent evidence from rodent and human studies

Abstract: Evidence suggests that spironolactone, a nonselective mineralocorticoid receptor (MR) antagonist, modulates alcohol seeking and consumption. Therefore, spironolactone may represent a novel pharmacotherapy for alcohol use disorder (AUD). In this study, we tested the effects of spironolactone in a mouse model of alcohol drinking (drinking-in-the-dark) and in a rat model of alcohol dependence (vapor exposure). We also investigated the association between spironolactone receipt for at least 60 continuous days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Clinical trials showed that melperone, a dopamine and serotonin receptor antagonist, has inconsistent effects on alcoholic craving 57,58 . Spironolactone, a mineralocorticoid receptor antagonist, reduced alcohol use in both rats and humans in a recent study 59 . Clomethiazole, a GABA receptor antagonist, also showed effect of treatment for alcohol withdrawal syndrome 60 .…”
Section: Discussionmentioning
confidence: 95%
“…Clinical trials showed that melperone, a dopamine and serotonin receptor antagonist, has inconsistent effects on alcoholic craving 57,58 . Spironolactone, a mineralocorticoid receptor antagonist, reduced alcohol use in both rats and humans in a recent study 59 . Clomethiazole, a GABA receptor antagonist, also showed effect of treatment for alcohol withdrawal syndrome 60 .…”
Section: Discussionmentioning
confidence: 95%
“…Trichostatin-a, a histone deacetylase inhibitor, showed effects on H3 and H4 acetylation and neuropeptide Y expression in the amygdala, and prevented the development of alcohol withdrawal-related anxiety in rats 54 . Spironolactone, a mineralocorticoid receptor antagonist, reduced alcohol use in both rats and humans in a recent study 55 . Clomethiazole, a GABA receptor antagonist, also showed an effect in treating alcohol withdrawal syndrome 56 .…”
Section: Discussionmentioning
confidence: 95%
“…To model alcohol binge-like drinking, rats were trained to self-administer a sweet alcohol (10% v/v ethanol, 3% w/v glucose, 0.1% w/v saccharin) solution and water under a free-choice, fixed ratio 1 (FR1) schedule of reinforcement in standard operant conditioning chambers (28 × 26 × 20 cm; Med Associates) ( 122 , 123 ). Alcohol-dependent rats were trained similarly except that they received unsweet alcohol (10% v/v ethanol) and water ( 54 , 120 ). Each operant response to the alcohol- or water-associated lever was reinforced with the delivery of 0.1 mL of fluid.…”
Section: Methodsmentioning
confidence: 99%